ANALYSIS OF FACTORS THAT INFLUENCE TRUST ISSUE SOCIETY ON LIFE INSURANCE PRODUCTS - Salwa Hayati Harahap; Nurul Inayah; Muhammad Arif (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
This study aims to analyze the factors influencing public trust in life insurance products in Indonesia. Using a qualitative approach, this study explores various factors contributing to low public trust, including a lack of understanding of life insurance products, negative experiences in the claims process, and the attitudes of insurance agents who lack transparency and tend to force sales. Furthermore, cultural and religious factors also impact public perceptions of life insurance. The results indicate that to increase public trust, insurance companies need to increase education and outreach, improve the transparency of product information, and optimize services, especially in the claims process. With these steps, it is hoped that public trust in life insurance products will increase, encouraging broader participation and the development of a healthier insurance industry in Indonesia.